African Entrepreneurship Challenges and Opportunities for Doing Business (Palgrave Studies of Entrepreneurship in Africa,, 2018)
This book outlines the unique challenges and opportunities of doing business in Africa, analysing how varying degrees of development across its countries affects entrepreneurship. Taking into account historical and cultural contexts, the authors approach the topic by evaluating the different possibilities of business opportunity in Africa. Insightful contributions explore an extensive range of African countries, discussing both formal and informal entrepreneurship, as well as the different factors that influence the growing economy of Africa. African Entrepreneurship will be of interest to anyone researching the potential of doing business in Africa, as well as entrepreneurs and policy-makers looking to expand their knowledge on how businesses are managed in this region.